Yoward the Meiji revolution : - Karube, Tadashi (Japan Publishing Industry Foundation for Culture, 2019)
This was not simply a transfer of political authority but instead signaled revolutionary transformation in Japan, including the abolition of the domains and the formation of a modern nation-state in the years that followed. A period of radical social change was ushered in with the abolition of the class system, the introduction of Western industrial and military technology, the development of mass media, and the establishment of constitutional government.